What Can I Do? - Strategies for Hope (FB Productions, 2015)
The HIV/AIDS Ministry and Messages of Gideon Byamugisha. Gideon Byamugisha is an ordained minister in the Anglican Church and Canon of St Paul’s Cathedral, Namirembe Diocese, Uganda. He is also HIV-positive. Through his life and his ministry, Gideon Byamugisha is an authentic prophetic voice, challenging people of faith to think more deeply and more creatively about their responses to the HIV epidemic. What can I do? is divided into 14 short segments on themes such as ‘Coping with stigma’, ‘Why be tested for HIV?’ and ‘Challenges for the Church’. There is also a Facilitator’s Guide which includes a transcript of the soundtrack, workshop guidelines and other tools for helping users get the most out of the video. Produced by FB Productions for the Strategies for Hope Trust.
Free